Study Of The Spicy Ulu At Nagari Air Bangis West Pasaman Regency - Aprila, Elsi; Zulfikar, Diki; Fridayati, Lucy; Indrayeni, Wiwik (Jurnal Pendidikan Tata Boga dan Teknologi, 2023)
The researh to learn and gain deeper knowledge about Ulu Podeh at Nagari Air Bangis. The research was conducted in December 2022-January 2023 in Nagari Air Bangis, Sungai Beremas district. To prevent the loss of this traditional cake, efforts are needed to preserve and introduce traditional products to the current generation. This study have purpose for identify the materials, equipment, and study processing techniques. The type of research used is qualitative with a case study approach. The research data obtained from the women leaders in Nagari Air Bangis, local community women who were able and skilled at making Ulu Podeh, and women who had made Ulu Podeh. Data collection tekhniques are carried out by observation, interviews, and documentation. Data analysis that is reduce data, presenting data, conclude and than verify. The results of this study is the the ingredeints for making Ulu Podeh are  glutinous rice, coconut milk, palm sugar, pepper, and salt. The tools used in processing Ulu Podeh are pan, stove, bowl, spatula, woden spoon, colander, utility try, and weighing scale. Method of cooking are boilling and roasted.